Clube sócio recreativos e outros lugares de lazer em Aracaju (1888-1915) - Santos, Jéssica Messias dos (2019)
This research seeks to identify and analyze the public and private spaces of the city of Aracaju between 1888 and 1915. We understand that Spanish spaces constitute privileged places for two different conflicts of a given historical period. Our working hypothesis is that no poster-abolition has had a period of disciplinary process and ordering of manifestations of the Brazilian national society - this is not the case here, in the city of Aracaju - that materializes in the regulation of carnival and the constitution of Private leisure clubs linked to sports, sports and public entertainment of a general administration.